2010
DOI: 10.1002/cne.22328
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic compartmentation of the cerebellar cortex in the chicken (Gallus domesticus)

Abstract: The chick is a well-understood developmental model of cerebellar pattern formation,but we know much less about the patterning of the adult chicken cerebellum. Therefore an expression study of two Purkinje cell stripe antigens-zebrin II/aldolase C and phospholipase Cbeta4 (PLCbeta4)-has been carried out in the adult chicken (Gallus domesticus). The mammalian cerebellar cortex is built around transverse expression domains ("transverse zones"), each of which is further subdivided into parasagittally oriented stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(99 citation statements)
references
References 115 publications
8
88
0
3
Order By: Relevance
“…Other groups have subsequently studied zebrin-IIimmunoreactive cerebellar compartments in order to carry out the following investigations: (1) interspecific comparison with the tammar wallaby (Macropus eugenii) (Marzban et al 2012), microchiropteran bats (Kim et al, 2009), hummingbirds (Aves: Trochilidae) (Iwaniuk et al, 2009), chicks (Gallus domesticus) (Marzban et al, 2010), pigeons (Columba livia) (Pakan et al, 2007; for an overview, see Marzban and Hawkes, 2011); (2) visualization of aldolase C with fluorescence through gene manipulation with the help of aldolase CVenus knock-in mice to facilitate studies on cerebellar compartmentalization (Fujita et al, 2014); (3) presentation of parasagittal stripes in the vermis which, complementary to zebrin II, are immunoreactive for neurofilament H (Demilly et al, 2011); (4) identification of links between the olivocerebellar projection and zebrin-immunoreactive compartments in the laboratory mouse (Sugihara and Quy, 2007) and in marmoset (Callithrix jacchus) (Fujita et al, 2010); (5) clarification of the role played by the helix-loop-helix (HLH) transcription factor early B-cell factor 2 (EBF2) (Croci et al, 2006); and (6) evaluation of the cerebellar connectivity in spinocerebellar ataxia type 1 (Solodkin et al, 2011). The second main research area of Wolfgang Knabe and colleagues, whose roots date back to the former anatomical department of Hans-Jürg Kuhn, continued previous projects on the retina, then served as a bridge between the retina and the forebrain, and, thereafter, was successively expanded to include the entire brain, spinal cord, neural crest, and the placodes.…”
Section: Cerebellummentioning
confidence: 99%
“…Other groups have subsequently studied zebrin-IIimmunoreactive cerebellar compartments in order to carry out the following investigations: (1) interspecific comparison with the tammar wallaby (Macropus eugenii) (Marzban et al 2012), microchiropteran bats (Kim et al, 2009), hummingbirds (Aves: Trochilidae) (Iwaniuk et al, 2009), chicks (Gallus domesticus) (Marzban et al, 2010), pigeons (Columba livia) (Pakan et al, 2007; for an overview, see Marzban and Hawkes, 2011); (2) visualization of aldolase C with fluorescence through gene manipulation with the help of aldolase CVenus knock-in mice to facilitate studies on cerebellar compartmentalization (Fujita et al, 2014); (3) presentation of parasagittal stripes in the vermis which, complementary to zebrin II, are immunoreactive for neurofilament H (Demilly et al, 2011); (4) identification of links between the olivocerebellar projection and zebrin-immunoreactive compartments in the laboratory mouse (Sugihara and Quy, 2007) and in marmoset (Callithrix jacchus) (Fujita et al, 2010); (5) clarification of the role played by the helix-loop-helix (HLH) transcription factor early B-cell factor 2 (EBF2) (Croci et al, 2006); and (6) evaluation of the cerebellar connectivity in spinocerebellar ataxia type 1 (Solodkin et al, 2011). The second main research area of Wolfgang Knabe and colleagues, whose roots date back to the former anatomical department of Hans-Jürg Kuhn, continued previous projects on the retina, then served as a bridge between the retina and the forebrain, and, thereafter, was successively expanded to include the entire brain, spinal cord, neural crest, and the placodes.…”
Section: Cerebellummentioning
confidence: 99%
“…After testing the upstream sequences of several genes that are expressed in Purkinje cells, we identified the promoter of the aldoca gene as a driver for Purkinje cellspecific gene expression. Aldolase C is the antigen of the zebrin II antibody, which marks a subset of Purkinje cells in the rodent and avian cerebellum (Lannoo et al, 1991b;Ozol et al, 1999;Marzban et al, 2010) and all the Purkinje cells in the cerebellum of teleosts, including zebrafish (Brochu et al, 1990;Lannoo et al, 1991a,b;Meek et al, 1992;Bae et al, 2009). Zebrafish has two copies of the aldolase c gene, and only one of them, aldoca (also known as aldocl), is expressed in Purkinje cells (Bae et al, 2009).…”
Section: Dendritic Morphology Of Purkinje Cells In the Zebrafish Cerementioning
confidence: 99%
“…Other markers that have been suggested and partly implemented in studies of neurotoxicity are Calbindin D28k and microtubule-associated protein-2 (Haworth et al, 2006). Calbindin D28k is a calcium-binding protein highly expressed in the cerebellum across various species, has been studied in chickens (Hunziker and Schrickel, 1988;Koszka et al, 1991;Marzban et al, 2010;Flace et al, 2014), and is associated with autism (Whitney et al, 2008) and hereditary ataxia (Koeppen et al, 2013) in humans. Microtubule-associated protein-2 has roles in neuronal growth and plasticity (Johnson and Jope, 1992), has been studied in chickens (Pinkas et al, 2015), and has been shown to be important in human traumatic brain injury (Mondello et al, 2012) and Rett syndrome (Johnston et al, 2001).…”
Section: Expanding the Use Of The Chicken Embryo Modelmentioning
confidence: 99%
“…However, the commercial broiler industry, which uses in ovo vaccination and drug treatments as strategies to defeat disease among flocks, has used monitoring of the respiratory system of the developing chicken in safety pharmacology testing of new vaccines. For , 1982;Fabene and Sbarbati, 2004;Aden et al, 2008Aden et al, , 2011Balaban et al, 2012;Mathisen et al, 2013 PET scan Structural and functional neuroimaging relevant in diffuse and focal brain disease MRI Morphology, measuring thickness of the cerebellar EGL and IGL Cerebellar abnormalities are clinically important causes of neurodevelopmental disabilities in premature babies, often manifested by cognitive, behavioral, attentional, and socialization deficits (Volpe, 2009) Biochemical Transcription factor PAX6 Important for cerebellar development and migration (Engelkamp et al, 1999); linked to autism (Umeda et al, 2010) Cicero andProvine, 1972;Hunziker and Schrickel, 1988;Koszka et al, 1991;Marzban et al, 2010;Mezey et al, 2012;Mathisen et al, 2013;Flace et al, 2014;Pinkas et al, 2015 Calbindin D28k Highly expressed in the cerebellum; associated with autism (Whitney et al, 2008) and hereditary ataxia in humans (Koeppen et al, 2013) Microtubule-associated protein-2…”
Section: Expanding the Use Of The Chicken Embryo Modelmentioning
confidence: 99%